Nocardiosis: a neglected infection - masoud keikha (Fasa University of Medical Sciences, 2017)
Genuse of Nocardia are aerobic, branching gram positive  and partially acid-fact bacteria. That ubiquitous in water, soil, dust and decaying vegetation in worldwide. This group of bacteria cause of Nocardiosis in humans particularly immune compromised patients. Paraffin baiting techniques best method for Isolation of Nocardia spp. from clinical specimens; Accurate identification of this bacteria important because in some cases can be misdiagnosed. We can take advantage of molecular and conventional methods to high accuracy identification of them.